Effect of Statin Intensity on the Progression of Cardiac Allograft Vasculopathy - Tracey M Ellimuttil (Radcliffe Medical Media, 2021)
Background: In the non-transplant population, hyperlipidaemia has shifted from targeting LDL goals to statin intensity-based treatment. It is unknown whether this strategy is also beneficial in cardiac transplantation. Methods: This single-centre retrospective study evaluated the effect of statin use and intensity on time to cardiac allograft vasculopathy (CAV) after cardiac transplantation. Kaplan–Meier and Cox proportional hazards regression survival methods were used to assess the association of statin intensity and median post-transplant LDL on CAV-free survival. Results: The study involved 143 adults (71% men, average follow-up of 25 ± 14 months) who underwent transplant between 2013 and 2017. Mean CAV-free survival was 47.5 months (95% CI [43.1–51.8]), with 29 patients having CAV grade 1 or greater. Median LDL was not associated with time to CAV (p=0.790). CAV-free survival did not differ between intensity groups (p=0.435). Conclusion: Given the non-statistically significant difference in time to CAV with higher intensity statins, the data suggest that advancing moderate- or high-intensity statin after cardiac transplantation may not provide additional long-term clinical benefit. Trial registration: Not applicable.